ICT exploitation in the mining and energy industry in Norte de Santander - Díaz, Nelly; Rodríguez, Judith P; Falla, B (Journal of Physics: Conference Series, 2020)
This article describes the results of the research paper "Characterization of ICT management of the Coal production sector in Norte de Santander against the guidelines of the current Strategic Plan for ICT in the Mining and Energy sector". The objective of the study details the characteristics of ICT management and its use in the unified environment of mining and energy sector companies in Norte de Santander. As a result, the basic architecture aligned with the ICT strategic plan of the mining and energy sector was identified, which includes: Document and archive management, process management, geographic information management, and security. In the same way, the limitations, capacities and state of maturity of the ICT management of the mission processes of the coal supply chain are specified, taking into account the level of integration with systems external to the sector such as the mining cadastre and the Ministry of Mines and Energy, among several and finally the information systems and tools used in decision making.
Ponencia de la conferencia "4th International Meeting on Applied Sciences and Engineering, EISI 2018; San Jose de Cucuta; Colombia; 3 September 2018 through 7 September 2018"
Keywords: Scopus(2); WOS(2)